More businesslike approach in telecentres - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
In the second half of the 1990s, multi-purpose community telecentres (MCTs) were established with heavy investments in many countries, including Burkina Faso, Cameroon, Guyana, Kenya, Mali, South Africa, Suriname and Uganda. Their services included...